Women’s Leadership in Islamic Boarding Schools: A Comparative Study of Islamic Boarding Schools in Indonesia, Malaysia, and Brunei Darussalam - Armila, Nizma (Eduprof : Islamic Education Journal, 2023)
It is common knowledge that men are the leaders of women, but Islam also encourages gender equality in education, which can be seen in the prophetic direction and the lives of salaf scholars, where at that time many female scholars emerged. Even so, religious boundaries must still be considered where in teaching and learning practice there can be no ikhtilat or mixing between men and women, therefore in the field of Islamic education, especially pesantren, it becomes a need for pesantren which only consists of women to the top. . In recent years, there has been a growing interest in women's leadership in these schools, as many Muslim women are seeking to become religious leaders.This comparative study aims to examine women's leadership in Islamic boarding schools in Indonesia, Malaysia, and Brunei Darussalam. The purpose of our study was to analyze the different leadership roles of women in Islamic boarding schools in these three countries. We use a qualitative approach combined with literature studies with interviews as a data collection technique. In addition, we used thematic comparative analysis to analyze the data collected from the interviews. The results are; in Indonesia, women often serve as heads of pesantren, focusing on collaborative, community-oriented leadership emphasizing service and mutual support. Conversely, female leadership in Malaysian Islamic schools is relatively rare, characterized by hierarchical structures and strict rule enforcement. Brunei Darussalam displays limited female leadership, with some exceptions following a conservative, values-centered approach. The study underscores the influence of cultural, social, and religious factors on women's leadership styles in Islamic educational institutions. The research highlights the need for further exploration of these dynamics, enabling the development of policies and practices that foster inclusive leadership environments within the context of Islamic teachings. At the end of this article will be presented in the form of a table about a comparison conclusion between Islamic Boarding School and Women Leadership in these specified countries for better understanding